EVALUATION OF PARTNERSHIP RELATIONSHIP IN ORGANIC VEGETABLE SUPPLY CHAIN IN CV. KURNIA KITRI AYU FARM MALANG - Nur Ocvanny Amir; Jabal Tarik Ibrahim; Gumoyo Mumpuni Ningsih; Zubdatul Asror (Socio-Economics/Agribusiness Department, 2020)
Market demand for organic vegetables at CV. Kurnia Kitri Ayu Farm continues to grow according to consumer needs. Market development is determined by the quality and continuity of the marketing distribution. To maintain this, in its business activities CV. Kurnia Kitri Ayu Farm established partnerships with several parties. The objectives of the research were 1) Knowing the supply chain of organic vegetables both in partnership and non-partnership with CV. KKAF, 2) Knowing the partnership patterns formed in the CV. KKAF, 3) Evaluating trust, commitment, communication, satisfaction, and dependence in organic vegetable supply chain partnerships. Respondents in this study consisted of the head of partner farmer groups, owners of CV. Kurnia Kitri Ayu Farm and the head of staff as a permanent partner for the home industry (baby care). The results showed 1) The flow of the organic vegetable supply chain consisted of the flow of goods, the flow of money, and the flow of information, 2) the partnership patterns contained in the organic vegetable supply chain, namely the plasma core partnership pattern, subcontracts, and general trading, 3) All parties in the supply chain on average feel very confident, have a very good commitment, communicate frequently, feel satisfied, and are very dependent on the performance of its partner members.